The impact of the Internet of Things on transportation in the supply chain - Jia, Zi-Xuan (2022)
In recent years, the Internet of Things is fully integrated into the current field of supply chain. Affected by the IoT, supply chain has also undergone corresponding transformation and change. Therefore, from the current situation, it is necessary to clarify the influence and specific role of the supply chain affected by the Internet of things and explore feasible improvement measures.